Imam Syafi’i dan Penolakan Metode Rasional dalam Ilmu Kalam - Fitria, Lailatul (Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
This article discusses Imam Syafi'i's thoughts on the idea of rational methods in kalam science. The rational method used by Mutakalimun, especially the Muktazilah school, placed reason in the dominance of extreme theology. This is clearly a concern for Imam Syafi'i that the belief in deifying reason is a very dangerous thing because it can damage the purity of the faith itself. From this problem, why did the rationalist method later become the main idea of criticism of the doctrine of rationalists such as the Muktazilah who deified the 'aql argument over the naql argument? From this, Imam Syafi'i opposes the existence of kalam scientific thinking methods with basics that are in accordance with the scope of science based on arguments for rejecting the rational approach as the only way to understand faith.